2016
DOI: 10.1002/erv.2446
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality Traits on Emotion Expression in Bulimic Spectrum Disorders: A Pilot Study

Abstract: Facial expressions are critical in forming social bonds and in signalling one's emotional state to others. In eating disorder patients, impairments in facial emotion recognition have been associated with eating psychopathology severity. Little research however has been carried out on how bulimic spectrum disorder (BSD) patients spontaneously express emotions. Our aim was to investigate emotion expression in BSD patients and to explore the influence of personality traits. Our study comprised 28 BSD women and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…These findings raise the question whether the persistent choice of inadequate caloric intake may be linked to disproportionate self‐control for AN‐R patients and more emotionally driven for AN‐BP patients (Steinglass & Walsh, ). Empirical studies on the effectiveness of treatment approaches focused on these features, such as overcontrol in the case of AN‐R patients (Lynch et al ., ; Lynch, Hempel, & Dunkley, ) or impulsivity for patients with bulimic‐spectrum disorders (Giner‐Bartolomé et al ., ; McClelland et al ., ; Val‐Laillet et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise the question whether the persistent choice of inadequate caloric intake may be linked to disproportionate self‐control for AN‐R patients and more emotionally driven for AN‐BP patients (Steinglass & Walsh, ). Empirical studies on the effectiveness of treatment approaches focused on these features, such as overcontrol in the case of AN‐R patients (Lynch et al ., ; Lynch, Hempel, & Dunkley, ) or impulsivity for patients with bulimic‐spectrum disorders (Giner‐Bartolomé et al ., ; McClelland et al ., ; Val‐Laillet et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large scale cohort study found that BN diagnosis and bulimic symptoms clustered together with mid-to-high incidence of novelty seeking [44]. Interestingly, a recent study investigating spontaneous facial expression and personality traits in BN and binge eating disorder, found increased positive facial expression was positive associated with novelty and reward seeking, while increased expression on anger was negatively associated with self-directedness [16]. However, it is of note that in the present study the BN participants were not significantly different from the HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Results reported that the BN group displayed significantly more negative facial affect than HC participants during the game [15]. Another similar study investigating spontaneous facial expressions in patients with BN and binge eating disorder during the same computer game, found that the patients expressed significantly less positive and negative facial affect than HCs [16]. Other studies investigating expression of positive and negative emotion in people with BN have found no differences between BN and HC participants in spontaneous positive and negative facial expressions in response to emotional film clips or during verbal expression of emotions when asked to talk about positive and negative emotional experiences [11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence indicating that patients with eating disorders (EDs) present difficulties expressing and regulating emotions (Giner-Bartolomé et al, 2016). Increasing evidence supports preceding emotion regulation (ER) models (Linehan, 1993; Gross, 1998) that postulate that ER difficulties often lead to the implementation of less appropriate strategies (e.g., maladaptive food intake or deliberate self-harm) to mollify unpleasant emotions.…”
Section: Introductionmentioning
confidence: 99%